Fear and Fascination in the Big City: Rilke's Use of George Simmel in The Notebooks of Malte Laurids Brigge - Neil H. Donahue (Studies in 20th & 21st Century Literature, 1992)
This essay examines Rainer Maria Rilke's The Notebooks of Malte Laurids Brigge (1910) as one corner in a triangle of reciprocal influence and affinity in early twentieth-century modernity consisting of Rilke, the sociologist Georg Simmel, and the art theorist Wilhelm Worringer. In the notes, this essay documents the biographical relations among the three, but in its text it demonstrates through textual analysis how Rilke's descriptions of Malte in Paris enact Simmel's categories of psychological response for man in the metropolis, as delineated in his essay "The Metropolis and Mental Life"(1903). Rilke's descriptions of Malte's attempts to overcome his fears of the metropolis coincide then with Worringer's thesis in his Abstraction and Empathy (1908) on the psychological origins of abstract art and Joseph Frank's later elaboration of that thesis into an aesthetics of spatial form.
Keywords: Rainer Maria Rilke; The Notebooks of Malte Laurids Brigge; twentieth-century; modernity; sociologist Georg Simmel; art theorist; Wilhelm Worringer; art; Malte in Paris; Paris; Simmel; metropolis; The Metropolis and Mental Life; thesis; Abstraction and Empathy; abstract art; Joseph Frank; spatial form